QTL mapping of multiple foliar disease and root-lesion nematode resistances in wheat - Rebecca S. Zwart; Thompson, J. P.; Milgate, A. W.; Bansal, Urmil K.; Williamson, P. M.; Raman, H.; Bariana, Harbans S. (Molecular Breeding, 2010)
A genetic linkage map, based on a cross between the synthetic hexaploid CPI133872 and the bread wheat cultivar Janz, was established using 111 F(1)-derived doubled haploid lines. The population was phenotyped in multiple years and/or locations for seven disease resistance traits, namely, Septoria tritici blotch (Mycosphaeralla graminicola), yellow leaf spot also known as tan spot (Pyrenophora tritici-repentis), stripe rust (Puccinia striiformis f. sp. tritici), leaf rust (Puccinia triticina), stem rust (Puccinia graminis f. sp. tritici) and two species of root-lesion nematode (Pratylenchyus thornei and P. neglectus). The DH population was also scored for coleoptile colour and the presence of the seedling leaf rust resistance gene Lr24. Implementation of a multiple-QTL model identified a tightly linked cluster of foliar disease resistance QTL in chromosome 3DL. Major QTL each for resistance to Septoria tritici blotch and yellow leaf spot were contributed by the synthetic hexaploid parent CPI133872 and linked in repulsion with the coincident Lr24/Sr24 locus carried by parent Janz. This is the first report of linked QTL for Septoria tritici blotch and yellow leaf spot contributed by the same parent. Additional QTL for yellow leaf spot were detected in 5AS and 5BL. Consistent QTL for stripe rust resistance were identified in chromosomes 1BL, 4BL and 7DS, with the QTL in 7DS corresponding to the Yr18/Lr34 region. Three major QTL for P. thornei resistance (2BS, 6DS, 6DL) and two for P. neglectus resistance (2BS, 6DS) were detected. The recombinants combining resistance to Septoria tritici blotch, yellow leaf spot, rust diseases and root-lesion nematodes from parents CPI133872 and Janz constitute valuable germplasm for the transfer of multiple disease resistance into new wheat cultivars.
Keywords: Pratylenchyus spp; Pyrenophora tritici-repentis; Rust diseases; Septoria tritici blotch; Synthetic hexaploid wheat; Triticum aestivum